An evaluation of a pilot specialist smoking cessation clinic in a mental health setting. (June 2019) - Davis, Amelia; Ngo, Hanh; Coleman, Mathew
Objectives: Smoking rates in people with mental illness in Australia remain alarmingly high whilst they have been declining in the general population. This study reviews a smoking cessation programme in a mental health service, as a pilot for future studies and program development. We aim to assess the effectiveness of this intervention and the ease of implementation after upskilling the clinical workforce. Methods: Part A – a retrospective analysis of patients attending the Smokers' Clinic, ( n = 44) over a period of 18 months. Part B– survey of ease of implementation and change in practice of the resident medical officers (RMOs; n = 8) following their clinical placement. Results: For the entire clinic population, the mean reduction in expired carbon monoxide was approximately 43%, with 34% of patients achieving abstinence. Females were 3.4 times more likely to be successful than males. Seventy-five per cent of RMOs found learning about nicotine dependence and smoking cessation 'easy', and 88% continued to offer smoking cessation after their placement. Conclusions: The Smokers' Clinic was successful in helping tobacco smokers with mental illness to reduce or cease smoking. Specialist skill and experience is not required to manage smoking cessation in a mental health setting.